Mapping the Sociocultural Implication on Tuberculosis Management and Control Programs: A Scoping Review - Handayani, Sri; Shaluhiyah, Zahroh; Widjanarko, Bagus; Susanto, Henry Setyawan; Agushybana, Farid (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
The effectiveness of tuberculosis (TB) management and control programs is influenced by several factors, including sociocultural problems that affect delays in diagnosis and treatment and increased transmission risk in the community. How people viewed diseases and seeking behavior was socially constructed. The scoping review aims to understand the extent and type of evidence about the sociocultural implications of TB management and control programs. To address the research questions, a scoping review was conducted following PRISMA ScR as a guideline. Articles were searched in PubMed, Scopus, Science Direct, and Google Scholar databases. Searches were conducted in October 2022. The CASP checklist was used to measure the article's quality before being reviewed. A total of 15 articles were included, nine (9) studies conducted in Africa, two (2) studies in Papua New Guinea, one (1) study in India, one (1) study in Brazil, one (1) study in Yemen, and one (1) study in Nepal. Most studies were based on individual interviews (7), and three (3) studies included traditional/faith healer perspectives. Three main themes have been identified; sociocultural factors affected TB prevention, sociocultural factors affected TB-seeking behavior, and sociocultural factors affected treatment adherence. The review discovered that community practices, norms, and attitudes regarding perceived sickness impact TB care and control. To be effective and meaningful for the target population, the intervention must be attentive to cultural differences.